2018
DOI: 10.1177/0963689718766362
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Responses are Sex Specific in Chronic Hypoxic–Ischemic Encephalopathy

Abstract: Neonatal hypoxic–ischemic encephalopathy (HIE) is increasingly recognized as a sexually dimorphic disease. Male infants are not only more vulnerable to ischemic insult; they also suffer more long-term cognitive deficits compared with females with comparable brain damage. The innate immune response plays a fundamental role in mediating acute neonatal HIE injury. However, the mechanism underlying the sex difference in chronic HIE is still elusive. The present study investigated the sex difference in HIE outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 50 publications
2
62
0
1
Order By: Relevance
“…Major target mechanisms of sex hormones are supposed to be regulation of neurotransmitter dysfunction and synaptic plasticity 144,145 . Nevertheless, preclinical reports demonstrating no sex differences in hormone levels but differences in outcome regarding early and late inflammatory responses and histological outcomes after neonatal HI 137,146 imply that additional intrinsic mechanisms may play a role in divergent susceptibility to the development of neurological deficits. This was demonstrated in in vitro cultures of isolated cells or brain slices revealing differences in cell death pathways and differentiation of specific hippocampal neuron subpopulations independent of the presence of hormones 147,148 .…”
Section: Sexual Dimorphismmentioning
confidence: 99%
See 1 more Smart Citation
“…Major target mechanisms of sex hormones are supposed to be regulation of neurotransmitter dysfunction and synaptic plasticity 144,145 . Nevertheless, preclinical reports demonstrating no sex differences in hormone levels but differences in outcome regarding early and late inflammatory responses and histological outcomes after neonatal HI 137,146 imply that additional intrinsic mechanisms may play a role in divergent susceptibility to the development of neurological deficits. This was demonstrated in in vitro cultures of isolated cells or brain slices revealing differences in cell death pathways and differentiation of specific hippocampal neuron subpopulations independent of the presence of hormones 147,148 .…”
Section: Sexual Dimorphismmentioning
confidence: 99%
“…In addition to perinatal immune challenges, neonatal HI induces long-lasting immune responses, which differ between genders. For instance, in adolescent male mice circulating levels of tumour necrosis factor (TNF)alpha were increased and males revealed more lymphocyte infiltration in injured brain hemispheres accompanied by reduced neurogenesis 137 . Regarding HI-induced atrophy and neurobehavioural deficits, gender differences were observed after neonatal HI in P9 mice with reduced brain atrophy in females while deficits in OF behaviour were increased, likely representing injury not detectable by volume measurements alone 138 .…”
Section: Sexual Dimorphismmentioning
confidence: 99%
“…Moreover, a large body of evidence has indicated that the stroke‐induced activation of inflammation is sexually dimorphic. After cerebral ischemia, microglia in female mice exhibit a more robust anti‐inflammatory response than those in males, and male mice exhibit an increase in CD11b immunoreactivity after MCAO . Clinically, patients with ischemic stroke present sex‐related differences in 3‐month outcomes and mortality, and sex‐related differences in prehospital data, molecular markers, and clinical variables have been documented .…”
Section: Different Sexual Microglia and Interventions For Strokementioning
confidence: 99%
“…After cerebral ischemia, microglia in female mice exhibit a more robust anti-inflammatory response than those in males, and male mice exhibit an increase in CD11b immunoreactivity after MCAO. [41][42][43] Clinically, patients with ischemic stroke present sex-related differences in 3-month outcomes and mortality, and sex-related differences in prehospital data, molecular markers, and clinical variables have been documented. 44 Further research has demonstrated a marked deregulation of microglial activation in ovariectomized and/or ERα knockout mice and increased vulnerability to ischemic injury, indicating that microglial heterogeneity poststroke is sex hormone-dependent.…”
Section: Ifferent S E Xual MI Crog Lia and Interventi On S For S mentioning
confidence: 99%
“…All procedures were approved by the Ethics Committee of Guangdong Pharmaceutical University and the guidelines of the Council on Animal Care were strictly followed. We established the HIE model by using the modified Rice-Vannucci method, which is widely accepted [13]. Briefly, 7-day-old pups were anesthetized with isoflurane and the common carotid artery (CCA) on the left side was ligated.…”
Section: Establishing a Model Of Neonatal Hiementioning
confidence: 99%